Biomechanical response of skeletal muscle to eccentric contractions - Richard L. Lieber (Elsevier, 2018)
The forced lengthening of an activated skeletal muscle has been termed an eccentric contraction (EC). This review highlights the mechanically unique nature of the EC and focuses on the specific disruption of proteins within the cell known as cytoskeletal proteins. The major intermediate filament cytoskeletal protein, desmin, has been the focus of work in this area because changes to desmin occur within minutes of ECs and because desmin has been shown to play both a mechanical and biologic role in a muscle's response to EC. It is hoped that these types of studies will assist in decreasing the incidence of muscle injury in athletes and facilitating the development of new therapies to treat muscle injuries. Keywords: Cytoskeleton, Eccentric contraction, Inflammation, Muscle injury, Muscle mechanics